A Study on The Impact of Career Development on The Quality of Work Life of Women BPO Employees in Thane - Naik, Kiran; Arte, Ashwini (SFIMAR Research Review, 2021)
Quality of Work Life (QWL) has been studied as a factor that has an impact on the overall life of an employee. Research has revealed that there are various factors that have an impact on the QWL of an employee. Among the various factors, the opportunities for development of career of an individual are considered critical. Various elements of career development like training, opportunities to apply individual employee’s talent, opportunities for personal development, the process of performance appraisal, promotions from within the organization to take up leadership positions which give opportunities for career advancement are considered for this study in an effort to find out whether the women BPO employees in Thane perceive that career development opportunities affect their QWL.